2014
DOI: 10.1177/1087057114526781
|View full text |Cite
|
Sign up to set email alerts
|

Development of the First Fluorescence Screening Assay for the SLC39A2 Zinc Transporter

Abstract: Zinc is an essential micronutrient that is crucial for many vital cellular functions such as DNA and protein synthesis, metabolism, and intracellular signaling. Therefore, the intracellular zinc concentration is tightly regulated by zinc transporters and zinc-binding proteins. The members of the SCL39 transporter family transport zinc into the cytosol. The SLC39A2 (hZIP2) protein is highly expressed in prostate epithelial cells and was found to be involved in prostate cancer development. Thus far, there is no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
1
16
1
Order By: Relevance
“…Altogether, these findings indicated that ZIP2 behaved as a Zn 2+ /HCO 3 − symporter (8). In contrast, prior work conducted in our laboratory suggested that ZIP2 activity is stimulated rather than inhibited by the presence of H + (13). In a more recent study, we showed that ZIP2-mediated transport in both microinjected Xenopus laevis oocytes and transiently transfected HEK293 cells is independent of both HCO 3 − - and H + -driving forces, but modulated by extracellular pH and voltage (14).…”
Section: Introductioncontrasting
confidence: 59%
“…Altogether, these findings indicated that ZIP2 behaved as a Zn 2+ /HCO 3 − symporter (8). In contrast, prior work conducted in our laboratory suggested that ZIP2 activity is stimulated rather than inhibited by the presence of H + (13). In a more recent study, we showed that ZIP2-mediated transport in both microinjected Xenopus laevis oocytes and transiently transfected HEK293 cells is independent of both HCO 3 − - and H + -driving forces, but modulated by extracellular pH and voltage (14).…”
Section: Introductioncontrasting
confidence: 59%
“…Although K m or normalized V max values between differing expression systems may vary, it is likely that trends, such as mutations that result in higher/lower affinities or changes in normalized V max , will be consistent between overexpression systems. Furthermore, considering that both micromolar and nanomolar K m values have been observed upon heterologous expression in mammalian cells as well as X. laevis oocytes, this suggests that either both affinities are present in vivo or that overexpression in both cell types gives equivalent artifacts (3,4,46). Therefore, analysis of hZIP4 transport experiments performed in X. laevis oocytes is a viable and valuable method to examine transport properties for this class of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the studies of Gaither et al, the functional activity of ZIP2 was found to be inhibited at pH levels below 7.0 (1). On the other hand, our fluorescence-based transport assay using transiently transfected HEK293 cells revealed that, at acidic pH (6.5), ZIP2-mediated Cd 2+ transport was greatly increased compared to pH 7.5(2). What could be the reason for this discrepancy?…”
mentioning
confidence: 87%
“…Recently, we published a screening assay that was established using the FLIPR Tetra high throughput microplate reader to identify specific modulators of ZIP2 as potential therapeutic hit or lead compounds (2). This assay is based on the use of a Ca 2+ -sensitive dye, Calcium 5 (Molecular Devices), which, in addition to Ca 2+ , binds Cd 2+ with high affinity.…”
Section: Introductionmentioning
confidence: 99%